Synthesis of 3-aroyl-4-aryl-1-isopropylamino-4-piperidinols and evaluation of the cytotoxicities of the compounds against human hepatoma and breast cancer cell lines. (August 2015) - Kucukoglu, Kaan; Mete, Ebru; Cetin-Atalay, Rengul; Gul, Halise Inci
Abstract Some 4-piperidinol derivatives were synthesized and their cytotoxicity was tested against human hepatoma (Huh7) and breast cancer (T47D) cells. Aryl part was changed as phenyl in 2a, 4-methylphenyl in 2b, 4-methoxyphenyl in 2c, 4-chlorophenyl in 2d, 4-fluorophenyl in 2e, 4-bromophenyl in 2f, 4-nitrophenyl in 2g and 2-thienyl in 3. Compounds were synthesized and reported for the first time by this study except 2a and 2d. Chemical structures were confirmed by 1H NMR, 13C NMR, IR, MS and elemental analyses. Compounds 2a (3.1 times), 2c (3.8 times), 2f (4.6 times), 2g (1.3 times) and 3 (3.2 times) had 1.3–4.6 times higher cytotoxic potency than the reference compound 5-FU against Huh7 cell line while all the compounds synthesized had shown lower activities against T47D cell line than 5-FU. In the light of these results, compounds 2a, 2c, 2f, 2g and 3 may serve as model compounds for further studies.